Mini-trampoline enhances cardiovascular responses during a stationary running exergame in adults - Rodrigues, Gusthavo A. A.; Rodrigues, Priscila C.; Silva, Fabiano F. da; Nakamura, Priscila M. [UNESP]; Higino, Wonder P.; Souza, Renato A. de (Inst Sport, 2018)
A new class of video game called exergame (EXG) has been used to promote physical activity and cardiovascular fitness, but EXGs are not as efficient as traditional aerobic exercises. However, auxiliary tools, such as the mini trampoline (MT), may enhance the physiological responses obtained by the EXG. The aim of this study was to compare the metabolic and cardiovascular responses of a stationary running EXG with and without an MT. Nineteen healthy males performed a treadmill test for the determination of VO(2)max and HRmax. In sequence, the VO2, HR, and METs were measured during the Free Run, a Nintendo Wii's stationary running EXG, according to two distinct protocols. One protocol used the traditional EXG (EXG-PT), and the other protocol used an MT during the EXG (MT-PT). The normalized data were analyzed by statistical software SPSS 20.0 using a t-test and ANOVA for repeated measures (p < 0.05). The results supported that stationary running EXG performed on an MT showed an increased intensity, in all variables analyzed, when compared with the traditional EXG. Furthermore, the MT-PT was classified as a vigorous-intensity exercise and EXG-PT as a moderate to vigorous intensity exercise. In conclusion, these findings support that the MT is a feasible auxiliary tool to enhance physiologic responses during a stationary running EXG.
Keywords: Mini-trampoline; Free Run; Nintendo Wii; VO2; Heart Rate; MET; Rehabilitation